Circulating tumour cells in patients with lung cancer universally indicate poor prognosis. (14th December 2022) - Jin, Fukang; Zhu, Lei; Shao, Jingbo; Yakoub, Mina; Schmitt, Lukas; Reißfelder, Christoph; Loges, Sonja; Benner, Axel; Schölch, Sebastian
Background: In lung cancer, the relevance of various circulating tumour cell (CTC) subgroups in different lung cancer subtypes is unclear. We performed a comprehensive meta-analysis to assess the prognostic value of CTCs in the different histological types of lung cancer, with particular respect to CTC subtypes, cut-offs and time points of CTC enumeration. Methods: We searched MEDLINE, Web of Science and Embase alongside relevant studies evaluating the prognostic value of CTCs in lung cancer patients. A random-effects model was used for meta-analysis, calculating hazard ratios (HRs), 95% confidence intervals and p-values. Results: 27 studies enrolling 2957 patients were included. CTC detection indicates poor prognosis, especially in small cell lung cancer (SCLC) patients (overall survival HR 3.11, 95% CI 2.59–3.73) and predicts a worse outcome compared to nonsmall cell lung cancer patients. Epithelial CTCs predict a worse outcome for lung cancer than mesenchymal CTCs or epithelial–mesenchymal hybrids. Conclusion: CTCs indicate poor prognosis in patients with primary lung cancer, with CTCs in SCLC having a more pronounced prognostic effect. The prognostic value of CTCs detected by different markers varies; most evidence is available for the strong negative prognostic effect of epithelial CTCs. This meta-analysis demonstrates that the prognostic value of epithelial CTCs is greater than that of mesenchymal CTCs in lung cancer. CTCs indicate poor prognosis in all subtypes of lung cancer; this effect increases with CTC detection thresholds. https://bit.ly/3dhlY0C